The Revenge of Seven: Lorien Legacies #5 - Lore, Pittacus (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2014)
The Garde, broken and divided, discover that the Mogadorians have commenced their ultimate invasion plans and will stop at nothing to thwart it.
"An I am number four book"--Spine.
Keywords: Extraterrestrial beings -- Fiction; Extraterrestrial beings -- Fiction; Science fiction